Analysis for Flow of an Incompressible Brinkman-Type Fluid in Thin Medium with Friction - Soumia Manaa; Salah Boulaaras; Hamid Benseridi; Mourad Dilmi; Sultan Alodhaibi (Journal of Function Spaces)
In this paper, we consider the Brinkman equation in the three-dimensional thin domain ℚε⊂ℝ3. The purpose of this paper is to evaluate the asymptotic convergence of a fluid flow in a stationary regime. Firstly, we expose the variational formulation of the posed problem. Then, we presented the problem in transpose form and prove different inequalities for the solution uε,pε independently of the parameter ε. Finally, these estimates allow us to have the limit problem and the Reynolds equation and establish the uniqueness of the solution.